Oxidative Stress Activates Endothelial Innate Immunity via Sterol Regulatory Element Binding Protein 2 (SREBP2) Transactivation of MicroRNA-92a. Issue 9 (3rd March 2015) - Chen, Zhen; Wen, Liang; Martin, Marcy; Hsu, Chien-Yi; Fang, Longhou; Lin, Feng-Mao; Lin, Ting-Yang; Geary, McKenna J.; Geary, Greg G.; Zhao, Yongli; Johnson, David A.; Chen, Jaw-Wen; et al.
<x xml:space="preserve">Abstract</x> Background— Oxidative stress activates endothelial innate immunity and disrupts endothelial functions, including endothelial nitric oxide synthase–derived nitric oxide bioavailability. Here, we postulated that oxidative stress induces sterol regulatory element–binding protein 2 (SREBP2) and microRNA-92a (miR-92a), which in turn activate endothelial innate immune response, leading to dysfunctional endothelium. Methods and Results— Using cultured endothelial cells challenged by diverse oxidative stresses, hypercholesterolemic zebrafish, and angiotensin II–infused or aged mice, we demonstrated that SREBP2 transactivation of microRNA-92a (miR-92a) is oxidative stress inducible. The SREBP2-induced miR-92a targets key molecules in endothelial homeostasis, including sirtuin 1, Krüppel-like factor 2, and Krüppel-like factor 4, leading to NOD-like receptor family pyrin domain-containing 3 inflammasome activation and endothelial nitric oxide synthase inhibition. In endothelial cell–specific SREBP2 transgenic mice, locked nucleic acid–modified antisense miR-92a attenuates inflammasome, improves vasodilation, and ameliorates angiotensin II–induced and aging-related atherogenesis. In patients with coronary artery disease, the level of circulating miR-92a is inversely correlated with endothelial cell–dependent, flow-mediated vasodilation and is positively correlated with serum level of interleukin-1β. Conclusions— Our findings suggest that SREBP2–miR-92a–inflammasome exacerbates endothelial dysfunction during oxidative stress. Identification of this mechanism may help in the diagnosis or treatment of disorders associated with oxidative stress, innate immune activation, and endothelial dysfunction.